Measurement of gas temperatures in dust-free and dusty argon discharges. (12th December 2019) - Pikalev, A; Pustylnik, M; Räth, C; Thomas, H
Abstract: Gas temperatures in an argon low-power capacitively-coupled rf discharge were measured by means of tunable diode laser absorption spectroscopy on 1 s 5 metastable states. It was shown that the uncertainty of the measurements in dust-free plasma could be minimized to 1 K. In the presence of dust, due to instabilities in the dust subsystem (e.g. dust density waves), the uncertainty of the temperature measurements increased several times. Nevertheless, an evidence of the gas temperature increase in the presence of dust was detected. This result suggests that the microparticle suspensions, immersed in the low-pressure plasmas, significantly modify the temperature fields of the neutral gas.